A Note on Exchange Stability - Field, H. (Review of Economic Studies, 1947)
A Note on Exchange Stability Get access H. Field H. Field Oxford Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 15, Issue 1, 1947, Pages 46–49, https://doi.org/10.2307/2295929 Published: 01 April 1947